Waiting times for diagnosis and surgery in a large obstetric-gynecological hospital in Italy. (13th November 2019) - Scaioli, G; Bert, F; Plazzotta, C; Corezzi, M; Voglino, G; La Valle, G; Rabacchi, G; Falco, S; Scarmozzino, A; SIliquini, R
Abstract: Issue: Diagnostic testing and surgical waiting times are related to quality of healthcare services. An extension of waiting times, indeed, could lead to a diagnostic or therapeutic delay, with potential consequences on patient health outcomes. Several policies have been implemented in different European countries in order to improve these indicators. Our study aims to analyse the waiting times of the largest obstetric and gynaecological hospital of Northern Italy, in order to identify potential issues in women's health services. Description of the problem: Data of "Sant'Anna Hospital" (Turin, Italy) about the waiting times in the period 2016-2017 for outpatient and surgical services addressed to women were collected. Specifically, number of health care procedures and mean waiting times (MWT) for "Obstetric-Gynaecological Echography" (OGE), "First Endocrinological Visit" (FEV), "First Gynaecological Visit" (FGV), "Surgical Intervention for Breast Cancer" (SIBC) and "Surgical Intervention for Uterus Cancer" (SIUC) were retrieved. Results were compared with the benchmark identified by the regional law. Results: A total of 21, 735 OGEs were performed, with a MWT of 3 days in 2016 and 5 days in 2017, below the benchmark (11 days). The total number of FEVs was 1, 234, with a MWT of 19 and 23 days in 2016 and 2017 respectively, again below the benchmark (30 days). The FGVs were 21, 096 with a MWT of 9 (2016) and 24 (2017) days (benchmark 30 days). The number of SIBCs (N = 89) performed within 30 days (benchmark) were 87 (98% of SIBCs), while SIUCs (N = 90) were 84 (93%). Lessons: The waiting times of the "Sant'Anna hospital" were, for all the performances considered, shorter than the regional benchmarks. This is an indicator of the quickness of diagnosis and treatment and, indirectly, of the quality of care. An international comparison among the main European hospitals should be encouraged in a perspective of continuous improvement of health care provided to European citizens. Key messages: Diagnostic testing and surgical waiting times are useful to assess the quickness and quality of health care provided in European hospitals. "Sant'Anna hospital", leader for women's health care, provides care with waiting times shorter than benchmarks. It would be interesting to compare its results with other large European hospitals.